Production of potassium hydroxide-activated biochar and its use as a filler in polylactic acid for food packaging - Serhat Balcı; Zeynep İrem Özyörü; Filiz Uğur Nigiz (Journal of Amasya University the Institute of Sciences and Technology)
Petroleum-containing packaging materials of the past and present have created serious ecological problems for the environment due to their resistance to biodegradation. In this context, researches have been conducted to promote the use of biodegradable films as an alternative to packaging materials. Among various biopolymers, poly(lactide) (PLA) has found application in the food industry owing to its promising properties and is currently one of the most industrially produced bioplastics. In this study, biomasses of olive pruning wastes, which are abundant in the Çanakkale region, were converted into biochar (BC) by slow pyrolysis, and their characterization was examined by adding them to PLA at different rates (5%, 10%, 15%, 20% by mass). Specific surface area analysis (BET), scanning electron microscopy (SEM) analysis, biochar yield, ash content, surface contact angles, and antimicrobial activity of film depending on the BC concentration were evaluated. As a result, potassium hydroxide (KOH) activated BC was successfully synthesized with a surface area of 1022 m2/g. The hydrophobicity of films was improved with increasing BC ratio. Also, the film shows good antimicrobial activity toward gram-negative bacteria.